Heterogeneity in imperfect inflation expectations: theory and evidence from a novel survey - Macaulay, A; Moberly, J (University of Oxford, 2022)
A given observation of uncertainty in expected inflation could be consistent with many different beliefs about how inflation is formed, with different implications for the aggregate transmission of shocks. We add novel questions to the Bundesbank Survey of Consumer Expectations to elicit (i) how persistent households perceive inflation to be, and (ii) how certain they are in their inflation perceptions. Combining these with existing survey questions, we infer laws of motion for expectations at the individual level. Based on averages alone, a standard model calibrated to our data predicts shocks to inflation generate small and transitory responses in expectations and consumption. Accounting for the large heterogeneity in expectation laws of motion across households, however, increases the transmission of inflation shocks to aggregate consumption through expectations by an order of magnitude, and substantially increases the persistence of the consumption response.